Sistem Monitoring Kualitas Air Pada PDAM Pangkalpinang Yang Terintergrasi dengan Website dan Smartphone - Yusfagiansyah, Ardhani; Azizah, Salsabila; Sulistyo, Eko; Andriyanto, Riki (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Technology plays a vital role in various industries, including water quality management, as it simplifies complex processes and enhances service quality. However, PDAM Pangkalpinang still uses manual methods to measure water quality. These methods have many drawbacks, such as being time-consuming and prone to human error. Manual measurements also make it difficult for PDAM to quickly detect changes in water quality, increasing the risk of distributing water that does not meet standards. Therefore, improving the effectiveness of water quality monitoring is crucial to ensure a clean water supply that meets health standards. This research aims to develop an automated real-time water quality monitoring system using various sensors: a pH sensor (4502c) to detect acidity and taste levels, a temperature sensor (thermistor), a turbidity sensor (AB209), and a gas odor sensor (MQ-136) to detect specific gas odors. The system utilizes ESP32 and Arduino Nano microcontrollers as processing units, integrated with IoT technology for remote monitoring. Testing results show high accuracy, with average errors of 0.61% for pH, 0.56% for temperature, 1.89% for turbidity, and 0.80% for gas odor detection. The collected data is automatically sent to Firebase and displayed through a web interface and smartphone application, enabling real-time water quality monitoring.